Poverty Alleviation In Disruption Era: A Study Of Social Entrepreneurship And John Dewey's Idea Of Humanity - Chandra, Maria Helena; Adam Yordan Leki Tamukun (International Journal of Economics, Business and Innovation Research, 2025)
Poverty as a complex problem that affects all levels of society, has become a global issue that requires serious attention. Its widespread impact, which includes low access to education, health, and economic opportunities, requires the search for effective and sustainable solutions. Poverty alleviation is not about economic improvement, but also about the fulfilment of human rights in order to realize a decent life for each individual. This is where the role of social entrepreneurship becomes very important, with a focus on creating innovative and socially impactful solutions that can address the root causes of poverty. John Dewey's idea of humanity, with its emphasis on the importance of education, community participation and moral values, provides a strong philosophical foundation for the practice of social entrepreneurship. This research aims to analyse the impact of social entrepreneurship in overcoming poverty, focusing on the role of education, access to resources, and community empowerment. The research method uses a literature study by linking the innovative model of social entrepreneurship with Dewey's idea of humanity as an alternative solution to solving the problem of poverty in Indonesia. The results provide empirical evidence of the effectiveness of social entrepreneurship in reducing poverty and improving people's quality of life. The implications of this research strengthen government, private, and community initiatives to encourage the growth and sustainability of social entrepreneurship business models based on the principles of humanity in every policy step taken. Moreover, social entrepreneurship is an effective force in creating sustainable and equitable social change for all stakeholders.